NAFTA Renegotiations: An opportunity for Canadian Dairy? - Eugene Beaulieu (The School of Public Policy Publications, 2018)
What are the implications of a renegotiated NAFTA for Canadian dairy producers? Many observers dread the prospect of even the slightest liberalization in the dairy sector. This paper takes a different perspective, arguing that opening Canada’s dairy sector would come with benefits not just for consumers, which is undeniable, but could also transform the industry and lead to a more productive dairy sector in Canada. Canadian dairy producers have been protected domestically through supply management and internationally through import-restricting border controls for over 40 years. This combination of domestic and foreign policies keeps Canadian dairy prices artificially high and allows producers to gain enormously from the system while hitting dairy consumers directly in the pocketbook. These policies are extremely costly for Canadian consumers and benefit the protected domestic dairy producers. Canadian international trade policies result in 200-percent tariffs on imports of many dairy products and almost 300-percent tariffs on over-quota imports of cheese. The OECD estimates that from 2010 to 2016, Canadian trade policy with respect to dairy and the “supply management system” annually transfers over US$2.9 billion from Canadian consumers and taxpayers to milk producers. This is extremely expensive for Canadian consumers and this transfer to Canadian dairy producers underscores why our trade partners have focused on the exorbitant tariffs that support this system. We argue that it is not only consumers that are hurt by the status quo, but that the industry itself can evolve and thrive from increased competition. According to standard trade theory, liberalizing trade in an industry like this leads the least productive producers to exit the industry as the most-productive producers increase market share and expand. These dynamics generate a more competitive and productive industry. We present evidence that these dynamics played out in Canada following the Canada-U.S. Free Trade Agreement (CUSFTA) and the North American Free Trade Agreement (NAFTA) and also in liberalized dairy industries in New Zealand and Australia. We argue that the massive economic rents earned by dairy producers in the essentially closed Canadian dairy sector means there is little competition in the industry, which has stifled growth and innovation in the sector. Liberalizing international trade in dairy will turn this around, increase competition in the industry and lead to a more productive and internationally competitive Canadian dairy sector while reducing the high cost of dairy faced by Canadian consumers. Liberalizing dairy will also be a strong signal to our trading partners that we are prepared to expend domestic political capital to improve NAFTA or other trade agreements. It has become clear that our trading partners have lost patience with our protectionist trade policies with respect to dairy. Multinational organizations such as the WTO have also highlighted the problems that these policies pose. Canada is feeling pressure to reform the system from trading partners who are hurt by supply management policies. Eliminating trade restrictions in the supply management sector would go a long way toward appeasing our trade partners and fulfilling our international commitments. Supply management policies are in violation of the spirit and, arguably, the letter of law in international trade agreements. In the recent Trans-Pacific Partnership (TPP) negotiations, Canada agreed to increase foreign access to its dairy market over a period of time by an estimated 3.25 per cent of its yearly milk production. This was a step in the right direction toward more competition in the sector. Canada should continue to push for reform in the dairy sector along the lines agreed to under TPP — but push even harder in the renegotiation of NAFTA. Unfortunately, Canadian politicians of all stripes have found that fixing supply management is a non-starter politically, with the powerful supply management lobby being such an effective lobby group. The TPP agreement provided the right opportunity to open the dairy industry. This is obviously good for Canadian consumers but will hurt some Canadian dairy producers. The negative impact on the politically sensitive dairy producers, primarily in southern Ontario and Quebec, has left the level of protection in the industry largely untouched for decades. Although some dairy producers will be hurt by opening the sector, the industry overall will thrive and become globally competitive. As demonstrated in the empirical literature of trade reform, and as we have observed in other Canadian industries that liberalized under CUSFTA and NAFTA, inefficient producers will close shop and more-productive producers will expand and prosper. The dairy trade liberalization that Canada agreed to under TPP should be the beginning and the NAFTA renegotiations are an opportunity for Canada to step up and do the right thing with respect to international trade in dairy while giving the Americans something they want in the negotiations. At the same time, it is an opportunity to weaken supply management and move toward dismantling it altogether.